PERAN PAMONG DALAM MENYELENGGARAKAN PEMBELAJARAN KREATIF PADA PROGRAM PAKET C DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS 1 KUPANG - Beroh, Asri Magdalena; Simbolon, Gallex; Mardani, Ambara Saraswati (Education For All, 2024)
The learning process has not been creative because of the low encouragement of learning citizens in participating in the learning process, because the children in LPKA are children who commit criminal acts so that they receive special guidance at LPKA and each child has a different character so that they have not been able to control themselves properly during the learning process such as making noise, like to be noticed, making it challenging for tutors to provide a positive and engaging learning environment in the classroom. The case study approach method is used in this research. The Special Child Development Institution (LPKA) Class 1 Kupang in Oesapa Barat Village, Kelapa Lima District, Kupang City, served as the study's location. Tutors, Learning Residents, and the Head of SPNF were the study's subjects. Interviews, observations, and documentation were used to collect data. Tutors have an important role in facilitating creative learning in the PAKET C program at the Special Child Development Institution (LPKA) Class 1 Kupang, according to the study results. The ability of tutors to facilitate creative learning is limited. The expense of producing different learning materials to enhance creative learning places restrictions on tutors. Students are less engaged in studying since the procedure is still tedious. Tutors employ conversation, face-to-face instruction, and observation to carry out the learning process. It might be inferred that since the teaching approach is still conventional, pupils are not as engaged in the current curriculum